Differential Responses of Soil Extracellular Enzyme Activities to Salinization: Implications for Soil Carbon Cycling in Tidal Wetlands. Issue 6 (13th June 2022) - Yang, Yang; Moorhead, Daryl L.; Craig, Hayley; Luo, Min; Chen, Xin; Huang, Jiafang; Olesen, Jørgen E.; Chen, Ji
Abstract: Rising sea levels are expected to cause salinization in many historically low‐salinity tidal wetlands. However, the response of soil extracellular enzyme activities to salinization in tidal wetlands and their links to soil organic carbon (SOC) decomposition are largely unknown. Here, we conducted a global meta‐analysis to examine the effect of salinization on hydrolytic and oxidative carbon‐acquiring enzyme activities and their relationships with SOC storage in tidal wetlands. The results showed that salinization reduced hydrolytic carbon‐acquiring enzyme activities by 33% but increased oxidative carbon‐acquiring enzyme activities by 15%. Meanwhile, salinization decreased SOC storage by 14%, and the change in SOC storage was negatively associated with oxidative carbon‐acquiring enzyme activities. These results indicate an important role for oxidative carbon‐acquiring enzymes in SOC loss in tidal wetlands. Moreover, the effect of salinization on oxidative carbon‐acquiring enzyme activities logarithmically declined with increasing salinization, implying that SOC loss was highly sensitive to even minor increases in salinity at the initial stage of salinization. Given increasing salinization over time with rising sea levels in most global tidal wetlands, our results suggest that SOC loss might be greater during early than later stages. Consequently, salinization‐induced SOC loss may be overstated in the long term if extrapolations are merely based on a constant SOC loss rate determined from short‐term studies. Future modeling frameworks should account for this changing sensitivity of microbially mediated SOC loss with increasing salinization over time. Key Points: Salinization reduced hydrolytic carbon‐acquiring enzyme activities but increased oxidative carbon‐acquiring enzyme activities Salinization decreased soil organic carbon storage, which was negatively associated with oxidative carbon‐acquiring enzyme activities Salinization‐induced soil carbon loss may be overestimated without considering changes in sensitivities of enzyme activities over time